Social psychology and gerontology: integrating theory to explain and intervene in age discrimination towards older people in Europe - Marques, S. (2016)
Today, age discrimination is one of the most fundamental forms of discrimination endured by Europeans. In an aging society this carries important consequences for the overall health and wellbeing of European citizens. This chapter discusses how integrating Social Psychology with Gerontology theorizing may contribute to the design of proper research and interventions dealing with this pressing social issue. To illustrate our discussion we present two case studies based on our findings from the “Experiences and expressions of ageism” module of the European Social Survey. Case 1 shows how the perception of age discrimination by older people mediates and helps to explain the effects of wealth inequality on older people’s subjective health. Case 2 presents compelling evidence showing that, among older people, identifying with being an older person is associated with poor health outcomes, especially in countries where older people’s status is lower. These findings are discussed in light of their implications for theory and practical intervention in this domain.